Controlling Homogenous Spherulitic Crystallization for High‐Efficiency Planar Perovskite Solar Cells Fabricated under Ambient High‐Humidity Conditions. Issue 49 (25th October 2019) - Angmo, Dechan; Peng, Xiaojin; Seeber, Aaron; Zuo, Chuantian; Gao, Mei; Hou, Qicheng; Yuan, Jian; Zhang, Qi; Cheng, Yi‐Bing; Vak, Doojin
Abstract: The influence of precursor solution properties, fabrication environment, and antisolvent properties on the microstructural evolution of perovskite films is reported. First, the impact of fabrication environment on the morphology of methyl ammonium lead iodide (MAPbI3 ) perovskite films with various Lewis‐base additives is reported. Second, the influence of antisolvent properties on perovskite film microstructure is investigated using antisolvents ranging from nonpolar heptane to highly polar water. This study shows an ambient environment that accelerates crystal growth at the expense of nucleation and introduces anisotropies in crystal morphology. The use of antisolvents enhances nucleation but also influences ambient moisture interaction with the precursor solution, resulting in different crystal morphology (shape, size, dispersity) in different antisolvents. Crystal morphology, in turn, dictates film quality. A homogenous spherulitic crystallization results in pinhole‐free films with similar microstructure irrespective of processing environment. This study further demonstrates propyl acetate, an environmentally benign antisolvent, which can induce spherulitic crystallization under ambient environment (52% relative humidity, 25 °C). With this, planar perovskite solar cells with ≈17.78% stabilized power conversion efficiency are achieved. Finally, a simple precipitation test and in situ crystallization imaging under an optical microscope that can enable a facile a priori screening of antisolvents is shown. Abstract : Film fabrication environment and anti‐solvent properties strongly influence the microstructure evolution of perovskite films. An ambient fabrication environment induces anisotropies in crystallization. The choice of antisolvent is critical to alleviating these anisotropies. The key is to induce uniform spherulitic crystallization to achieve robust pinhole‐free films possessing grains, crystallinity, crystallographic phases, and crystallite orientations unaffected by the processing environment.